2020
DOI: 10.3390/ma13214789
|View full text |Cite
|
Sign up to set email alerts
|

A Custom-Made Orthodontic Mini-Implant—Effect of Insertion Angle and Cortical Bone Thickness on Stress Distribution with a Complex In Vitro and In Vivo Biosafety Profile

Abstract: Background: Orthodontic mini-implant failure is a debatable subject in clinical practice. However, the most important parameter to evaluate the success rate of mini-implant is the primary stability, which is mainly influenced by cortical bone thickness (CBT) and insertion angle. Materials and methods: Three-dimensional finite element models of the maxilla were created and a custom-made, self-drilling, tapered mini-implant was designed. For the pull-out test, 12 simulations were performed, sequentially increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Additionally, metal alloys were studied and their bioavailability could be established by using the HET–CAM assay, with the possibility of analyzing the impact of certain metals released in the tested media [ 58 ]. In this regard, our research group recently demonstrated the lack of irritative potential and completed the biocompatibility data of dental materials such as mini-implants [ 25 , 39 ], thus confirming the benefits of this assay in toxicity studies for materials with topical application including dental use.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, metal alloys were studied and their bioavailability could be established by using the HET–CAM assay, with the possibility of analyzing the impact of certain metals released in the tested media [ 58 ]. In this regard, our research group recently demonstrated the lack of irritative potential and completed the biocompatibility data of dental materials such as mini-implants [ 25 , 39 ], thus confirming the benefits of this assay in toxicity studies for materials with topical application including dental use.…”
Section: Discussionmentioning
confidence: 87%
“…In brief, fertilized eggs from Gallus gallus domesticus were sprayed with ethanol (70%) to ensure disinfection of the eggshell and afterwards the eggs were placed in an incubator at 37 °C and high humidity. Further, a slightly modified protocol developed by our group was employed [ 25 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Contrarily, Liu et al [ 44 ] reported that mini-implant insertion with an oblique angle increased primary stability. Popa et al [ 15 ] used the finite element analysis to reveal that the cortical bone stress showed lowest value and highest stability when the mini-implant had a 30° implantation angle, and when the cortical bone thickness was 1 mm. Meanwhile, when the cortical bone thickness was 2 mm, the cortical bone stress had the lowest value with an implantation angle of 90°.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate more effective correction of severe malocclusions and dentofacial discrepancies [ 1 , 2 , 3 , 4 ], such as en-masse retraction of anterior teeth [ 2 , 5 ], molar uprighting [ 6 ], maxillary expansion [ 7 , 8 , 9 , 10 ], skeletal open bite or deep bite correction [ 11 , 12 ], and anteroposterior discrepancy correction [ 13 , 14 ]. The successful use of TSADs in the clinic is highly related to their stability [ 15 , 16 , 17 ]. Several studies consider miniscrew design according to the requirements of clinical stability [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to mention that the success rate of orthodontic implants is based on several key factors, such as the implantation procedure employed, dental material features, implant topography, and design [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%